KAJIAN ETNOBOTANI RAMUAN PASCA MELAHIRKAN PADA MASYARAKAT ENGGANO [The Ethnobotanical Study of Postpartum Concoction on Enggano People] - Royyani, Mohammad Fathi; Lestari, Vera Budi; Agusta, Andria; Efendy, Oscar (BERITA BIOLOGI, 2018)
This research was aimed to discover the traditional knowledge of Enggano people when using plants as concoction after giving birth. Data was collected through in depth interview, open-ended, and literature studies. The results showed that Enggano people used specific plants as concoction in childbirth process. There were two types of the concoction. The first was used after giving birth to 40 days, jarak pagar or tiarak (Jatropha curcas L.). The second was used after 40 days to 60 days or after recovery, such as dukung anak (Phyllanthus niruri Linn.), kumis kucing (Orthosiphon stamineus Benth.), temu lawak (Curcuma xanthoriza Roxb.), alang-alang (Imperata cylindrica (L) P. Beauv.), banana (Musa sp.), kencur (Kaempferia galanga L.), turmeric (Curcuma longa L.), and ginger (Zingiber officinale Roscoe). Results from our literature studies confirmed the efficacy of plants used by Enggano people is scientifically acceptable. Further study on phytochemical aspects of these medicial plants is therefore required to be carried out.